Sistem Informasi Layanan Kesehatan Di Puskesmas Sukarami - Yovita, Sukma; Sanmorino, Ahmad; Faradillah (Jurnal Ilmiah Informatika Global, 2025)
Sukarami Health Center in Palembang is a public health facility owned by the local government of Palembang City, located on Jalan Kebun Bunga RT.37 RW. 05, Kebun Bunga Village, Sukarami Subdistrict, Palembang. In providing healthcare services, sometimes the information regarding these services is not easily accessible by the residents of Sukarami. This is because the Sukarami Health Center does not have its own independent website and has been relying solely on the Palembang Health Department’s website, which results in outdated information that cannot be directly communicated to the public. Additionally, during healthcare services, residents or patients often struggle to find out what services are available at the Sukarami Health Center. The staff and personnel at the Sukarami Health Center also face challenges in managing patient medical records. This is because patient data is not integrated, and they currently rely only on medical cards and handwritten medical record books, making the data prone to damage or loss. This study was conducted to simplify the service process at Sukarami Health Center, allowing patients to access healthcare information and have online consultations from home. The system being developed is also intended to facilitate the staff at the health center in managing service data and patient medical records. This health service information system is built as a website using the prototype software development method and the black-box testing method to ensure that the system is tested according to the input and output requirements from the users.